2018
DOI: 10.14218/jcth.2018.00001
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Spontaneous Bacterial Peritonitis in Patients with Cirrhotic Ascites

Abstract: Background and Aims: Spontaneous bacterial peritonitis (SBP) is a serious complication of liver cirrhosis and a prognostic model to predict it is needed. This study was designed to test the ability of different laboratory tests and the new scoring system by Wehmeyer and colleagues (consisting of age, C-reactive protein (CRP) and platelet count) to predict it.Methods: Three-hundred patients admitted to the National Liver Institute, University of Menoufia, Egypt (2015–2016) with liver cirrhosis and ascites were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 28 publications
14
20
2
Order By: Relevance
“…Our study showed that there was a significant difference between the mean values of BT, creatinine, INR, serum WBC, serum albumin and PLT in the SBP group compared to those without SBP. The mean values of BT, creatinine, INR, and serum WBC were significantly higher, and the mean PLT was significantly lower, in a group of 59 patients with SBP from a study with 300 patients with liver cirrhosis (14). But in contrast with our study results, there was no statistically significant difference in serum albumin values between the groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study showed that there was a significant difference between the mean values of BT, creatinine, INR, serum WBC, serum albumin and PLT in the SBP group compared to those without SBP. The mean values of BT, creatinine, INR, and serum WBC were significantly higher, and the mean PLT was significantly lower, in a group of 59 patients with SBP from a study with 300 patients with liver cirrhosis (14). But in contrast with our study results, there was no statistically significant difference in serum albumin values between the groups.…”
Section: Discussioncontrasting
confidence: 99%
“…In the current study, the measurement of serum or ascitic nitrous oxide did not add a benefit in SBP diagnosis. Patients with SBP had higher serum CRP level, which is consistent with the other studies [12,14,19]. Furthermore, serum hsCRP was higher in SBP patients in accord with Guler et al [6] study.…”
Section: Discussionsupporting
confidence: 91%
“…The hsCRP has a higher sensitivity than CRP. Patients with SBP show elevated CRP levels that decrease with treatment [12,14,19]. Only one study by Guler et al [6] assessed the role of serum hsCRP in nonneutrocytic ascites.…”
Section: Discussionmentioning
confidence: 99%
“…As regarding, liver profile and kidney function tests in our study, there were disturbances in both liver profile and kidney functions reported among cirrhotic ascitic patients with and without SBP which can be explained by liver cell failure that agreed with Metwally et al, [19].…”
Section: Fig 1 Positive Correlation Between Nlr Car and Ascitic Neutrophil Count After Sbp Treatmentsupporting
confidence: 91%